2008
DOI: 10.1148/radiol.2471061982
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer: Role of Pretreatment MR in Predicting Outcome after External-Beam Radiation Therapy—Initial Experience

Abstract: Purpose-To retrospectively determine if pretreatment endorectal magnetic resonance (MR) imaging findings are predictive of outcome in patients who undergo external-beam radiation therapy for prostate cancer.Materials and Methods-Committee on Human Research approval, with waiver of the requirement for informed consent, was obtained for this HIPAA-compliant study. Eighty men with biopsy-proved prostate cancer (mean age, 59 years; range, 47-75 years) who underwent endorectal MR imaging of the prostate prior to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 25 publications
(22 reference statements)
2
41
0
Order By: Relevance
“…In concordance with data in prior studies ( 27,29,31 ), we found that extracapsular extension was an independent predictor of treatment failure, but seminal vesicle invasion was not predictive of treatment response (28)(29)(30). This was a surprising fi nding, as seminal vesicle invasion is widely believed to be associated with larger tumors with a poorer prognosis; our study is small and may have been underpowered to…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In concordance with data in prior studies ( 27,29,31 ), we found that extracapsular extension was an independent predictor of treatment failure, but seminal vesicle invasion was not predictive of treatment response (28)(29)(30). This was a surprising fi nding, as seminal vesicle invasion is widely believed to be associated with larger tumors with a poorer prognosis; our study is small and may have been underpowered to…”
Section: Discussionsupporting
confidence: 91%
“…Researchers in some studies have investigated the use of these techniques for prediction of patients' outcome following radiation therapy (27)(28)(29)31,46 ). The results of these studies have suggested that imaging fi ndings can be used to predict treatment response.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a multivariate analysis of 67 patients, SVI on MRI and MRSI prior to external-beam radiation therapy predicted a worse prognosis [87] . The group demonstrated that the presence and degree of ECE on MRI significantly predicted post-treatment metastatic recurrence [88] . A study of 36 consecutive patients demonstrated a significantly greater area under the ROC curve (Az) for combined T2WI and DWI (Az = 0.879, P < 0.01) as compared to T2WI (Az = 0.612).…”
Section: Therapy Responsementioning
confidence: 98%